Protection of allergic rhinitis in mice via the colonic release of butyrate from butyrylated starch - Zhen Chen; Yang Liu; Chenyu Chen; Xing Lin; Yihan Wei; Qingqing Xu; Shancai He; Yuanteng Xu (Journal of Functional Foods, 2024)
Butyrate has potential beneficial effects on allergic rhinitis (AR). However, the effect of AR mice via the colonic butyrate is still unclear. We investigated the potential mechanism of colonic butyrate derived from butyrylated starch intervention to improve the atopy and regulate gut microbiota in AR mice. The results demonstrated that butyrylated starch significantly increased the levels of colonic butyrate, and downregulated serum OVA-sIgE, IL-4, and IL-5, and improved symptoms in AR mice. In addition, the proportion of Treg cells in mesenteric lymph nodes and the levels of IL-10 and TGF-β in the serum were elevated after butyrylated starch intervention. Moreover, butyrylated starch promoted the enrichment of beneficial genera in AR mice, such as Lactobacillus, and alleviated the composition and structural disorder of gut microbiota in AR mice. In conclusion, butyrylated starch demonstrated a preventive effect on AR, possibly by modulating the gut microbiota and promoting Treg cell function.